The discourse of Islam and other religions by early ʿulamā’ in the Malay world - Abdul Jalil, Mohd. Noh (Akademi Pengajian Islam, UM, 2021)
This paper analyzes the discourse of early ʿulamā’ in the Malay world such as Nūr al-Dīn al-Rānīrī and ʿAbdul Rāūf al-Sinkilī on Islam and other religions. Early ʿulamā’ in the Malay world wrote numerous intellectual works for the need of local as well as international audiences. The history of religions in the Malay world revealed interesting facts on the diversity of religions existed and practiced by the local people. The question now is on how early ʿulamā’ in the Malay world addressed the presence and influence of religions other than Islam during the early period of Islam in the Malay world. In order to find answer to this question, this paper analyzes topic of interest written by these early ʿulamā’. Analysis is also expanded to the discourse between local ʿulamā’ and their counterparts all over the world. Special focus is given to the discourse on religions other than Islam written by early ʿulamā’ in the Malay world in order to understand their priority at that time. This paper concludes that the discourse in the writings of early ʿulamā’ in the Malay world correspond with their counterparts worldwide. The main discourse is still on the fundamental teachings of Islam. Nevertheless, discourse on religions other than Islam was not totally neglected. The limited discourse on religions other than Islam in the works of early ʿulamā’ in the Malay world implicitly tells us about the priority of early ʿulamā’ in the Malay world at that time in propagating the messages of Islam to the local people.